The antibodies 3D12 and 4D12 recognise distinct epitopes and conformations of HLA-E - Brackenridge, Simon; John, Nessy; Früh, Klaus; Borrow, Persephone; McMichael, Andrew J. (Frontiers in Immunology, 2024)
The commonly used antibodies 3D12 and 4D12 recognise the human leukocyte antigen E (HLA-E) protein. These antibodies bind distinct epitopes on HLA-E and differ in their ability to bind alleles of the major histocompatibility complex E (MHC-E) proteins of rhesus and cynomolgus macaques. We confirmed that neither antibody cross-reacts with classical HLA alleles, and used hybrids of different MHC-E alleles to map the regions that are critical for their binding. 3D12 recognises a region on the alpha 3 domain, with its specificity for HLA-E resulting from the amino acids present at three key positions (219, 223 and 224) that are unique to HLA-E, while 4D12 binds to the start of the alpha 2 domain, adjacent to the C terminus of the presented peptide. 3D12 staining is increased by incubation of cells at 27°C, and by addition of the canonical signal sequence peptide presented by HLA-E peptide (VL9, VMAPRTLVL). This suggests that 3D12 may bind peptide-free forms of HLA-E, which would be expected to accumulate at the cell surface when cells are incubated at lower temperatures, as well as HLA-E with peptide. Therefore, additional studies are required to determine exactly what forms of HLA-E can be recognised by 3D12. In contrast, while staining with 4D12 was also increased when cells were incubated at 27°C, it was decreased when the VL9 peptide was added. We conclude that 4D12 preferentially binds to peptidefree HLA-E, and, although not suitable for measuring the total cell surface levels of MHC-E, may putatively identify peptide-receptive forms.